Ventricular Catheter Tract Hemorrhage as a Risk Factor for Ventriculostomy-Related Infection. Issue 1 (11th July 2019) - Kim, Julie; Lee, James; Feng, Rui; Chartrain, Alexander; Sobotka, Stanislaw; Griffiths, Stephen; Weiss, Nirit; Dangayach, Neha; Bederson, Joshua; Mayer, Stephan A; Gordon, Errol
Abstract: BACKGROUND: Ventriculostomy-related infection (VRI) is a feared complication of external ventricular drain (EVD) placement. Although many contributing factors to VRI have been examined, little is known whether there is an association between ventriculostomy-related catheter tract hemorrhage (VCTH) and VRI. OBJECTIVE: To evaluate risk factors for VRI and assess possible correlations with VCTH. METHODS: We performed a retrospective analysis of patients with EVD placement in a neurocritical care unit between 2011 and 2015. VRI was defined as clinical signs of infection with a positive cerebrospinal fluid gram stain and isolation of cerebrospinal fluid culture. VCTH was diagnosed by computed tomography immediately after EVD insertion. RESULTS: A total of 247 patients with EVD were identified during the 5-yr study period. An association between VCTH and gram-negative VRI was identified ( P = .02). Ten percent (25 of 247 patients) developed a VRI, and 7% (18 of 247 patients) had a VCTH. Of the 25 patients with VRI, 20% (n = 5) had a VCTH, compared to 6% (n = 13) of 222 patients who had an EVD placed but did not develop VRI. There were no significant differences in demographic and clinical factors except for multiple EVD insertions ( P < .00001), EVD duration ( P < .001), and hospital length of stay ( P < .001). CONCLUSION: VCTH is a potentially significant risk factor for VRI. Further analysis will be needed to confirm the strength of this association, and to delineate the possible mechanisms by which tract hemorrhage may serve as a nidus for bacterial penetration into the central nervous system. Graphical Abstract: